Bibliographic Transition in France: - Gianolio, Christelle (Organizacija znanja, 2023)
This article presents the current state of bibliographic transition in France, the approach and the organization that were applied to make library catalogues compatible with semantic web technologies and bibliographic data on the web. In order to achieve this goal, it is necessary to move to entity-based cataloguing built on the IFLA LRM model. After a thorough study of the RDA standard, which was the first step to take, France has chosen to keep some autonomy and create a national cataloguing standard, RDA-FR, which is an Anglo-American standard adapted to the French context. In order to implement this change, the Bibliographic Transition programme has been assigned to two national bibliographic agencies with three operational pillars representing the three facets of the program: standardisation, training and support for the evolution of systems and data. The choices and the issues are given in details, as well as the missions and achievements of the groups. This organisation has been established to ensure a regular flow of information between the operational and strategic levels on one side and between different groups on the other side. Overall consistency is one of the key features of the programme whose role is to bring together and represent all French libraries and French cultural institutions while taking into account their needs and the needs of their users.
Keywords: cataloguing rules; cataloguing training; IFLA Library Reference Model (IFLA LRM); integrirani knjižnični sistemi; Katalogizacijska pravila; library management systems; Resource Description and Access (RDA); usposabljanje za katalogizacijo